2017
DOI: 10.1248/bpb.b17-00131
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Alleviates Depressive-Like Behaviors <i>via</i> Down-Regulating Inflammatory Cytokines Induced by Chronic Restraint Stress in Mice

Abstract: The purpose of the present study was to investigate whether ketamine's rapid antidepressant effects were associated with its anti-inflammatory actions and to explore the underlying molecular mechanism. Depressive-like behaviors was induced in mice using chronic restraint stress (CRS) method. Anti-depressive effects of ketamine were evaluated by forced swimming tests (FST) and sucrose preference test (SPT). Subsequently, brain tissue was harvested to investigate inflammatory response in the hippocampus via inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 43 publications
7
56
0
5
Order By: Relevance
“…Since neuroinflammation plays a causative role in the pathophysiology of depression, targeting this pathway may hold promise for targeted therapy. Furthermore, several studies have proven that acute or chronic RS up-regulates pro-inflammatory cytokines associated with the development of depressive-like behaviors (56,57). Similarly, we found that RS led to the up-regulation of NF-κB, TNF-α, and IL-6 protein expressions in the PFC and HIP subregions.…”
Section: Discussionsupporting
confidence: 77%
“…Since neuroinflammation plays a causative role in the pathophysiology of depression, targeting this pathway may hold promise for targeted therapy. Furthermore, several studies have proven that acute or chronic RS up-regulates pro-inflammatory cytokines associated with the development of depressive-like behaviors (56,57). Similarly, we found that RS led to the up-regulation of NF-κB, TNF-α, and IL-6 protein expressions in the PFC and HIP subregions.…”
Section: Discussionsupporting
confidence: 77%
“…The role of P2X7Rs as essential activators of NLRP3 was also convincingly demonstrated by showing that UCMS elevates hippocampal P2X7R levels (Tan et al, 2017). The selective P2X7R antagonist Brilliant Blue G (BBG) attenuated the increase of immobility time in TST and FST in mice after activation of the inflammasome by LPS (Ma et al, 2014).…”
Section: The P2x7r Triggers Neuroinflammation and Subsequent Mood Dismentioning
confidence: 91%
“…Chronic inflammatory reactions cause neurons apoptosis in brain regions associated with emotion regulation such as hippocampus, 132,133 leading to impairment of synaptic plasticity. Ketamine could normalize abnormal neurobehaviours induced by neuroinflammation through regulating the interleukin (IL)‐1β, tumour necrosis factor (TNF)‐α and IL‐6 134 . In rodent model, ketamine would reverse the increase in IL‐1β and TNF‐α caused by lipopolysaccharide (LPS), shortening the immobility time significantly in FST and promoting hippocampal neurogenesis 135 .…”
Section: Synaptic Plasticitymentioning
confidence: 99%